17th Annual Vancouver Folk Music Festival - Vancouver Folk Music Festival Societyet al (1994)
Jericho Beach Park 17TH ANNUAL VANCOUVER FOLK MUSIC FESTIVAL/ Early Bird Weekend tickets available only until June 25th 1993 prices!/ Over 200 performers from 16 countries Austin Lounge Lizards TEXAS Black Umfolosi ZIMBABWE Bob Bossin BC Boukan Ginen HAITI Wild Child Butler ALABAMA/ONTARIO Craobh Rua IRELAND D'Gary MADAGASCAR Derivative Duo WASHINGTON Ani DiFranco with Andy Stochansky NEW YORK Danny Dill TENNESSEE Tammy Fassaert BC Mo Field BC The Flying Bulgar Klezmer Band ONTARIO Roy Forbes BC Paul Geremia MASSACHUSETTS Tami Greer BC Guitar Gabriel NORTH CAROLINA Wayne Henderson & Helen White VIRGINIA Veda Hille BC Si Kahn NORTH CAROLINA Irshad Khan INDIA/ONTARIO Kin Lalat GUATEMALA/BC Die Knodel AUSTRIA John Koerner MINNESOTA Les Freres Labri QUEBEC Penny Lang QUEBEC Eddie Lawrence ALABAMA/NEW YORK Mara! AUSTRALIA Simon Mayor & Hilary James ENGLAND The Robert Minden Ensemble BC Pamela Morgan NEWFOUNDLAND Morin Khuur CHINA Peter Ostroushko & Dean Magraw MINNESOTA Mark Perry BC Plankerdown Band NEWFOUNDLAND Psychograss CALIFORNIA Punjabi By Nature ONTARIO Q'Jom Tze GUATEMALA/BC Quartette - Sylvia Tyson, Cindy Church, Caitlin Hanford & Colleen Peterson ONTARIO Rawlins Cross NEWFOUNDLAND/NOVA SCOTIA The John Reischman Group CALIFORNIA/BC Peter Rowan & The Rowan Brothers CALIFORNIA Roots Punta Rock BELIZE Rumillajta BOLIVIA Claudia Schmidt MICHIGAN Toronto Tabla Ensemble ONTARIO Uzume Taiko Ensemble BC Peter Paul Van Camp MANITOBA Wapistan (Lawrence Martin) ONTARIO Michael Wex ALBERTA/ONTARIO The Whiteley Brothers ONTARIO Takeo Yamashiro JAPAN/BC Radim Zenkl CZECHOSLOVAKIA and more.or less/ 6 daytime stages SAT & SUN 3 evening concerts FRI, SAT & SUN Little folks area with special children's programming and activities A food area as diverse as the music./ TICKETS To mail, phone or fax orders, and for more information, please contact us at the VANCOUVER FOLK MUSIC FESTIVAL 3271 Main Street, Vancouver, BC V5V 3M6 604 879.2931 FAX 604 879.4315 In Vancouver, tickets are also available at Highlife Records 251.6964 or TicketMaster 280.4444/ TicketMaster Tickets available at all TicketMaster locations throughout BC, charge by phone in Vancouver at 280.4444, in Washington and Oregon at 206 628.0888./ Vancouver-Highlife Records 1317 Commercial Drive 251.6964 Victoria-Boomtown CD Rentals 711 Yates Street 380.5090 Seattle, WA-Red & Black Books 432 - 15th Avenue East 322.7323 Cellophane Square Records 1311 NE 42nd Street 634.2280 Bellevue, WA-Cellophane Square Records 169 Bellevue Square 454.5059 Bellingham, WA-The Landing 1307 - 11th Street 647.1307 Mount Vernon, WA-Northern Lights 402 South Street 634.2280 Portland, OR-KBOO Community Radio 20 SE 8th Avenue 231.8032/ Sponsored by the Vancouver Folk Music Festival Society with assistance from the Vancouver Board of Parks and Recreation; the City of Vancouver-Office of Cultural Affairs, Social Planning Department; the Government of British Columbia through the Cultural Services Branch-Ministry of Small Business, Tourism and Culture; Government of Canada through Canadian Heritage-Cultural Initiatives Program; and Employment and Immigration Canada. Thanks Folks!/ JULY 15, 16 & 17 1994 JERICHO BEACH PARK/ design eyebyte 669.5625 collage gek-bee siow/ The bird is the word.the Rivingtons